2014
DOI: 10.2214/ajr.13.11325
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function in Type 2 Diabetes Mellitus and the Association With Coronary Artery Calcium Score: A Cardiac MRI Study

Abstract: C a r d io p u l m o n a r y I m ag i ng • O r ig i n a l R e s e a rc hThis article is available for credit. This research was financially supported by Project "DoIT," which is cofinanced by the European Community Fund FEDER through COMPETE. rosis [10], which can be detected noninvasively by MDCT.Coronary artery disease is commonly cited as a mechanism underlying diastolic dysfunction [11]. Many of the same factors that contribute to atherosclerosis may also produce LV diastolic dysfunction by either direct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…To define the volume-time curve index of CMR, the PER indicates the peak rate of left ventricular ejection, which is evaluated from the maximal LV ejection rate defined by the maximal change in the LV volume between sequential temporal phases (△volume/△phase). The PFR indicates the maximal LV filling rate defined by maximal change in LV volume between sequential temporal phases (△volume/△phase) [14]. PER/EDV represents the PER when normalized to EDV, and PFR/EDV represents the PFR when normalized to EDV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To define the volume-time curve index of CMR, the PER indicates the peak rate of left ventricular ejection, which is evaluated from the maximal LV ejection rate defined by the maximal change in the LV volume between sequential temporal phases (△volume/△phase). The PFR indicates the maximal LV filling rate defined by maximal change in LV volume between sequential temporal phases (△volume/△phase) [14]. PER/EDV represents the PER when normalized to EDV, and PFR/EDV represents the PFR when normalized to EDV.…”
Section: Discussionmentioning
confidence: 99%
“…DM2 has an adverse effect on coronary microvascular dysfunction and left ventricular diastolic function. Previous research has found that DM2 patients had a lower PFR than normal individuals, indicating the presence of impaired myocardial relaxation and increased myocardial stiffness; consequently, the abnormal LV filling in DM2 patients is closely associated with abnormal myocardial perfusion [14]. In the study conducted by Zeidan et al, volume-time curves of CAD patients revealed significantly PFR [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] found that the PFR values in patients with Type 2 DM were significantly lower than those in the control group. In our study with G-SPECT, the PFR in patients with DM was also significantly lower than that in patients without DM.…”
Section: Discussionmentioning
confidence: 99%
“…11 Using PFR normalized to LV stroke volume, Graca et al have reported LVDD in patients with T2DM and CAD compared with those without CAD. 12 Despite evidence of an abnormal LV diastolic filling profile associated with CAD, less is known about the influence of a lifestyle modification program on LV diastolic filling and diastolic function in patients with CAD and with varying levels of glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%